Interstitial deletion of band 3q25. Issue 5 (May 1997) - Slavotinek, A M; Huson, S M; Fitchett, M
Abstract : Interstitial deletions of the long arm of chromosome 3 are rare. We report a man with an interstitial deletion involving band 3q25. To our knowledge, this is the first patient to be described with this cytogenetic abnormality.